Aerospace series. Steel X4CrNiMo16-5-1. Air melted. Hardened and tempered. Sheets and plates. 0, 3 mm ? a ? 50 mm. 900 MPa ? Rm ? 1 050 MPa. (4th July 2022) - British Standards Institution,
No abstract available